Case for diagnosis - Fabre,Andréa Buosi (2014)
Intravascular papillary endothelial hyperplasia is a benign vascular lesion caused by proliferation of endothelium. It is reactive to thrombotic or inflammatory stimuli in the vessel wall.We report the case of a 14-yearold male patient with a violet-colored erythematous tumoral lesion of progressive growth in the occipital region. The diagnosis of intravascular papillary endothelial hyperplasia (IPEH) was confirmed by clinical and histopathological findings. Total lesion exeresis was performed with no recurrence up to date. IPEH presents clinical importance due to its clinical and histological resemblance to angiosarcoma. In order to differentiate it from angiosarcoma, distinguishing features of the benign disease should be considered, such as lack of cellular atypia and rare mitotic activity.Prognosis is good.